Economic Sentiment Index - Chasi, Andrea (2025)
This research develops an Economic Sentiment Index (ESI) for Ecuador, based on daily economic news published on national web platforms between 2019 and 2025. The indicator is generated through a reproducible process that applies sentiment analysis models in Spanish, combining lexical and deep learning approaches. The results show that the PySentimiento model achieves the best performance and that the ESI exhibits significant correlations with key indicators of consumer confidence, business expectations, and economic activity. The study highlights the value of news analysis as a high-frequency and low-cost tool for macroeconomic monitoring in emerging economies.